Оцінка значущості персоналії при включенні до біографічних словників у контексті новітніх інформаційних технологій - Вернік, Ю.В. (Українська біографістика, 2010)
Analyzed some of the approaches to the defi nition of criteria for inclusion of staff in the UBA. A measure to determine the signifi cance of personality as an index reference to it in electronic resources, identifi ed characteristics that affect the average value of the index. Revised the list of priorities on the preparation of secondary indexes personalities included in the UBA.